2012
DOI: 10.1021/ct300493y
|View full text |Cite
|
Sign up to set email alerts
|

Improving Generalized Born Models by Exploiting Connections to Polarizable Continuum Models. II. Corrections for Salt Effects

Abstract: A previous analytical investigation of the generalized Born (GB) implicit solvation model is extended to solvents of nonzero ionic strength. The GB model with salt effects (GB-SE) is shown to resemble the Debye-Hückel-like screening model (DESMO), a polarizable continuum model (PCM) that we have recently developed for salty solutions. DESMO may be regarded either as a generalization of the conductor-like PCM (C-PCM) that extends C-PCM to electrolyte solutions or alternatively as a generalization of Debye-Hücke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…The coupling provides a way to include polarization in the solvent (and implicitly in the solute) without including a large number of explicit solvent molecules, and this may be a way to retain high accuracy in terms of solvation energies without a large reduction in computational efficiency. 40 The C-PCM model, on the other hand, is a continuum model, where all solute charges interact with all the surface charges. The exact definition of the cavity surface depends on the specific model 7,9 but will usually be allowed to change if the solute structure changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coupling provides a way to include polarization in the solvent (and implicitly in the solute) without including a large number of explicit solvent molecules, and this may be a way to retain high accuracy in terms of solvation energies without a large reduction in computational efficiency. 40 The C-PCM model, on the other hand, is a continuum model, where all solute charges interact with all the surface charges. The exact definition of the cavity surface depends on the specific model 7,9 but will usually be allowed to change if the solute structure changes.…”
Section: Discussionmentioning
confidence: 99%
“…(8). 40 Equations 10and (13) involve the inversion of AGB and A † GB having the same (N, N) dimension as the original kernel ABC. The increase in computational cost by coupling the GB model to the BC equations is thus expected to be very small.…”
Section: Ggb(mentioning
confidence: 99%
“…113,149 It has been suggested that the "optimal" atomic radius for a given atom likely ought to vary as a function of its partial atomic charge, 150,151 and probably as a function of the solvent's dielectric constant as well. 94,132,152,153 In quantum chemistry, the latter effect is generally neglected whereas the former is handled solvent probe sphere solvent-accessible surface (SAS) van der Waals (vdW) surface solvent-excluded surface (SES) vdW F I G U R E 2 Various constructions of the solute cavity surface, using a set of atomic spheres (in gray) whose envelope defines the van der Waals (vdW) surface, shown in black. The solvent-accessible surface (SAS, in green) is defined either by augmenting the atomic radii by a probe radius (R A = R vdW,A + R probe ) or equivalently as the center point of the probe sphere as it rolls over the vdW surface.…”
Section: Solute Cavitymentioning
confidence: 99%
“…This procedure effectively forces the pairwise GB ansatz in Equation (4.4) to reproduce the exact electrostatic energy defined by the continuum electrostatics problem, and the values of R A determined in this way have been called the "perfect" Born radii. 419,423 However, the procedure just described is not a practical one, although it can be used to generate data sets of exact pairwise interactions, 23,152,153 which might suggest new analytical forms to replace Equation (4.5). 23,152,153,425,426 For practical purposes the radii R K f g are usually determined using surface integration procedures, the most popular of which is 418,419,422,424 R…”
Section: Smx and Other Sasa-based Modelsmentioning
confidence: 99%
“…A great deal of effort has gone into testing variants of these ideas against both numerical Poisson calculations and against experiment . Extensions have been made to include salt effects at the Debye‐Huckel level of approximation …”
Section: Implicit Solvent Modelsmentioning
confidence: 99%